Foot soak therapy with warm ginger for families with elderly hypertension - Taufik Hidayat; Any Zahrotul Widniah; Annisa Febriana (Universitas Muhammadiyah Magelang, 2022)
One of the primary factors that most affects the development of cardiovascular disease is hypertension. According to the Framingham Heart Study, hypertension is now more common than it was in the past. There are 757 patients with hypertension in the Astambul Health Center's service area in the Banjar Regency as of 2021. The aim of the community service conducted in Astambul District families with geriatric hypertension is to reduce blood pressure by giving the patients' foot soak therapy with warm ginger. The community service method is carried out by carrying out the preliminary stages, the implementation—which includes counseling, blood pressure measurements, demonstrations and evaluation. The family and the elderly enthusiastically participating in soaking feet in warm red ginger water is proof that the activities were carried out well in accordance with the program design that had been created. Additionally, following the intervention, the systolic blood pressure dropped by 0.4 mmHg. The participants reported experiencing at ease and relaxed after soaking their feet in warm red ginger water, which reduced tension in their body muscles.